Coma With Absent Brainstem Reflexes and a Burst Suppression on EEG Secondary to Baclofen Toxicity - Farhat, Sahar; El Halabi, Tarek; Makki, Achraf; Atweh, Samir F.; Nasreddine, Wassim; Beydoun, Ahmad (Frontiers in Neurology, 2020)
Abstract Baclofen, a muscle relaxant prescribed for the alleviation of symptoms of spasticity acts primarily at the spinal level but with high doses, it penetrates the blood-brain barrier and can result in prominent central nervous depression. Baclofen toxicity has been associated with a variety of symptoms ranging from dizziness to deep coma. We report the clinical course, management and outcome of a case of baclofen overdose who presented in deep coma with loss of brainstem reflexes and a burst suppression pattern (BS) on his electroencephalogram (EEG). In addition, we reviewed the presentation and outcomes of all reported cases of baclofen toxicity with a BS on EEG to evaluate if those cases share a common clinical presentation and for the presence of signs and symptoms that would help the clinician to consider this diagnosis. There appears to be a common clinical picture associated with severe baclofen toxicity consisting of deep coma associated with loss of all brainstem reflexes including pupillary reactivity, frequent association with seizures/myoclonic jerks and a BS on EEG. The outcome is generally good, and serial EEGs are recommended to document a reversal of the abnormal electrographic features.